(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Living life of human being has been changed today likewise there are many sectors which are connected to human being have been also changed. Higher Education System is moved toward ICT based teaching and learning and library is a part of learning system and supporting system to teaching area. To making effectiveness among both area, there are many e-resources are available and simultaneously print resources are used. But as per the changing needs of user community academic libraries are moved towards new paradigm shift for fulfillment of academic needs of their users. There are more advantages as compared to its demerits. Therefore such resources are become important today with various approaches.